2021
DOI: 10.1108/jpif-10-2020-0114
|View full text |Cite
|
Sign up to set email alerts
|

Physical and climate change-related risk identification in valuation practice: an Australian perspective

Abstract: PurposeThe purpose of this research is to investigate Australian property valuers' identification and consideration of physical risks to properties in valuation practice. The research further explores valuers' considerations of climate change-related risks.Design/methodology/approachThe research approach comprised an online survey of Australian valuers who were members of the Australian Property Institute. The online survey included structured and unstructured questions to explore types and extent of risk inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…Similar guidance is provided by other bodies such as the Australian Property Institute (Warren-Myers and Cradduck, 2021).…”
Section: Professional Standards Guidance and Regulationmentioning
confidence: 86%
See 2 more Smart Citations
“…Similar guidance is provided by other bodies such as the Australian Property Institute (Warren-Myers and Cradduck, 2021).…”
Section: Professional Standards Guidance and Regulationmentioning
confidence: 86%
“…(2019) found no consistent approach in how professionals in Australia, China, Germany, United Kingdom and USA reflected flood risk in their advice. Warren-Myers and Cradduck (2021) concluded that inadequate identification, consideration and reporting of climate change risks could be attributed to a lack of guidance from professional bodies as to what is required, as well as inadequate data sources with which to evaluate the risks. Lamond et al.…”
Section: Professional Standards Guidance and Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Craddock et al. , 2020; Warren-Myers and Craddock, 2022; Warren-Myers et al. , 2020 a, b), energy efficiency and the effectiveness of Energy Performance Certificates (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More recent environmental sustainability and real estate research has added significantly to the depth of this research around critical issues such as climate change risk issues in real estate/valuation (e.g. Craddock et al, 2020;Warren-Myers and Craddock, 2022;Warren-Myers et al, 2020 a, b), energy efficiency and the effectiveness of Energy Performance Certificates (e.g. Fuerst et al, 2011a, b, c), decarbonisation frameworks/ strategies (e.g.…”
Section: Literature Review Esg and Environmental Sustainabilitymentioning
confidence: 99%